Penguatan identitas nasional lewat boikot produk asing: dampak dan peluang nya bagi negara indonesia - Rani, Nesa Maulin Eka (Maliki Interdisciplinary Journal, 2025)
In the era of globalization, the influx of foreign products into Indonesia has raised concerns about the loss of economic independence and the erosion of national identity. The boycott movement of foreign products has become one of the community’s strategies in responding to the issue, especially when it is related to global humanitarian conflicts such as the Palestinian struggle. This study examines the impact and opportunities of the boycott movement on strengthening national identity and developing domestic industries. The results show that boycotts can encourage the consumption of local products, strengthen the national spirit, and become a form of public diplomacy. However, challenges remain, such as the readiness of local industries, dependence on global supply chains, and the risks of international trade relations. Therefore, the boycott movement must be accompanied by affirmative strategies, such as support for MSMEs, local product digitization campaigns, and wise protective policies. With a strategic approach, boycotts can be a tool for economic transformation as well as a strengthener of Indonesia’s national identity.